Gender and autistic traits modulate implicit motor synchrony. - Miao Cheng; Masaharu Kato; Chia-Huei Tseng (PLoS ONE)
Interpersonal motor synchrony during walking or dancing is universally observed across cultures, and this joint movement was modulated by physical and social parameters. However, human interactions are greatly shaped by our unique traits, and self-related factors are surprisingly little studied in the context of interpersonal motor synchrony. In this study, we investigated two such factors known to be highly associated with motor coordination: gender and autistic traits. We employed a real-world task extending our understanding beyond laboratory tasks. Participants of the same gender were paired up to walk and chat in a natural environment. A cover story was introduced so that participants would not know their walking steps were being recorded and instead believed that their location was being tracked by a global positioning system (GPS), so they would ignore the motor recording. We found that the female pairs' steps were more synchronized than those of the males, and higher autistic tendencies (measured by the autism-spectrum quotient) attenuated synchronous steps. Those who synchronized better had higher impression rating increase for their walking partners (measured by interpersonal judgement scale) than those who synchronized less well. Our results indicated that the participants' joint movements were shaped by predisposed traits and might share similar mechanism with social functions such as empathy.